Chemical composition of deep sea manganese deposits determined at Kennecott Corporation during the 1967-1969 period - James E Andrews; Günther Friedrich (PANGAEA, 2022)
During the 1967-1968 period chemical analysis of both major and trace elements was performed on manganese nodules, crusts and micronodules on a large number of cores taken by the Lamont-Doherty Observatory during various cruises of the R/V Vema and the R/V Robert D. Conrad. Methods of analysis were a combination of Wet chemistry and Atomic Absorption Analysis (AAS). Most of the samples are related to buried deposits inside sediment columns. This data was released to Dr. W. M. Ewing, the then Director of Lamont Geological Observatory who handed the results to S. K. Addy for his review and research work (see, related document: S. K. Addy, 1978). It was later included in the SIO Nodule Database and finally transferred into the NOAA-MMS database.